Parental willingness to vaccinate their daughters against human papilloma virus and its associated factors in Woldia town, Northeast Ethiopia - Sisay Melese Bittew; Seteamlak Adane Masresha; Getahun Fentaw Mulaw; Mohammed Ahmed Yimam; Abiot Alebel Zimamu; Atnaf Alem Abriham; Atitegeb Abera Kidie (Frontiers in Global Women's Health, 2024)
BackgroundThe cells of the cervical epithelial wall are the source of the malignant tumor caused by the human papilloma virus (HPV) known as cervical cancer. In 2018, Ethiopia implemented the HPV vaccine specifically targeting girls aged 9–14 years. This vaccination initiative serves as an effective preventive measure against cervical cancer, provided that parents express a positive inclination to have their daughters vaccinated as part of the program.ObjectiveThe aim of the study was to assess parental willingness to vaccinate their daughters against human papillomavirus and its associated factors in Woldia town, Northeast Ethiopia.MethodsA community-based cross-sectional study was conducted among 414 parents of daughters aged 9–14 years between 10 and 25 January 2023. Respondents were selected by a systematic sampling method and a face-to-face interview was conducted to collect data. Data were entered into Epi Data version 4.6 and exported to SPSS version 25 for analysis. Multivariable analyses were used to examine the association between dependent and independent variables. The adjusted odds ratio (AOR), 95% confidence interval (CI), and p-value <0.05 were used to determine statistical significance.ResultsA total of 410 study participants with a response rate of 99% were included in the study, and approximately 72.9% (95% CI: 68.3–77.2) of them were willing to vaccinate their daughters. This study found that parents with a family history of cervical cancer screening (AOR = 3.27, 95%; CI = 1.38–7.74), secondary and above educational status (AOR = 2.72, 95% CI = 1.29–5.73), good knowledge of the human papilloma virus vaccination (AOR = 3.00, 95% CI = 1.70–5.28), and favorable attitude toward the human papilloma virus vaccine (AOR = 4.40, 95% CI = 2.45–7.88) were significantly associated with parental willingness to vaccinate their daughters against human papilloma virus.RecommendationIn this study, most parents were willing to vaccinate their daughters against human papilloma virus. The significant determinants of parental willingness to their daughter's human papilloma virus vaccination were family history of cervical cancer screening, level of education, and knowledge and attitude toward the human papilloma virus vaccine. Therefore, health information regarding the human papillomavirus vaccination with an emphasis on raising community awareness should be designed.